Media studies : key issues and debates - Eoin Devereux (New Delhi Sage Publications, 2007)
Bringing together a range of renowned and newly emerging scholars in the field, including a Preface by Denis McQuail, this book examines eighteen key issues within contemporary media studies. Written in an accessible student-friendly style, Media Studies: Key Issues and Debates is an authoritative landmark text for undergraduate students and teachers alike. Each chapter begins with a concise definition of the concept(s) under investigation, followed by a discussion of the current state of play within research on the specific area. Chapters contain case-studies and illustrative materials from Europe, North America, Australia, and beyond. Each chapter concludes with annotated notes, which guide readers in terms of future study.
Keywords: General; Mass Media